Impact of Perioperative Immunonutrition on Complications in Patients Undergoing Radical Cystectomy: A Retrospective Analysis. (May 2021) - Cozzi, Gabriele; Musi, Gennaro; Milani, Martina; Jemos, Costantino; Gandini, Sara; Mazzoleni, Ludovica; Ferro, Matteo; Luzzago, Stefano; Bianchi, Roberto; Omodeo Salé, Emanuela; de Cobelli, Ottavio
Introduction: Radical cystectomy (RC) is the gold standard treatment for patients with muscle-invasive or refractory non-muscle invasive bladder cancer. It is estimated that approximately 64% and 13% of RC patients experience any complication and major complications, respectively. Specialized immunonutrition (SIM) aims to reduce the rates of complications after RC. We reported surgical complication rates in RC patients who received (SIM group) versus who did not receive (no-SIM group) perioperative SIM. Moreover, we investigated factors associated with complications after RC. Material and Methods: This is a retrospective cohort study of 52 patients who underwent RC between April 2016 and December 2017. Overall, 26 (50%) patients received perioperative SIM. We recorded age, gender, Charlson Comorbidity Index (CCI), body mass index (BMI), Malnutrition Universal Screening Tool (MUST) score, unintentional weight loss (UWL), SIM drinks consume, surgical approach, urinary diversion, neoadjuvant chemotherapy (NAC), use of total parenteral nutrition (TPN), final pathology, length of stay (LOS), and complications. Results: SIM was associated with higher rates of documented infections ( P  = .03). Conversely, post-operative ileus was associated with higher rates of overall infections ( P  = .03). Median LOS was comparable within the 2 groups. Overall, 4 (15.38%) versus 0 (0%) patients in SIM versus no-SIM group were readmitted to hospital ( P  = .03). Age, CCI, NAC, and TPN were not associated with complication rates. Conclusions: SIM is not associated with lower rates of post-operative complications in RC candidates. Moreover, higher rates of documented infections were observed in the SIM group. Patients with post-operative ileus experienced more infections. Age, CCI, NAC, and TPN were not predictive of complications.